Isolation, Antimicrobial Effect and Metabolite Analysis of Bacillus amyloliquefaciens ZJLMBA1908 against Citrus Canker Caused by Xanthomonas citri subsp. citri - Xinru Ke; Zilin Wu; Yucheng Liu; Yonglin Liang; Manling Du; Ya Li (Microorganisms, 2023)
Citrus canker caused by Xanthomonas citri subsp. citri is a devastating bacterial disease with severe implications for the citrus industry. Microorganisms possessing biocontrol capabilities against X. citri subsp. citri offer a highly promising strategy for healthy citrus management. In the present study, a broad-spectrum antagonist strain ZJLMBA1908 with potent antibacterial activity against X. citri subsp. citri was isolated from symptomatic lemon leaves, and identified as Bacillus amyloliquefaciens. Cell-free supernatant (CFS) of strain ZJLMBA1908 also exhibited remarkable antimicrobial activity, especially suppressing the growth of X. citri subsp. citri and Nigrospora oryzae, with inhibition rates of 27.71% and 63.75%, respectively. The antibacterial crude extract (CE) derived from the CFS displayed effective activity against X. citri subsp. citri. A preventive treatment using the CE significantly reduced the severity and incidence of citrus canker in a highly susceptible citrus host. Additionally, the CE maintained activity in the presence of protease and under a wide range of temperature and pH treatments. Applying high-performance liquid chromatography (HPLC) to separate and purify the CE resulted in the discovery of one highly potent anti-X. citri subsp. citri subfraction, namely CE3, which could completely inhibit the growth of X. citri subsp. citri. Liquid chromatography–electrospray ionization–mass spectrometry (LC–ESI–MS) analysis revealed that CE3 mainly consisted of palmitic acid, surfactin C15, phytosphingosine and dihydrosphingosine. Taken together, the results contribute to the possible biocontrol mechanisms of B. amyloliquefaciens ZJLMBA1908, as well as providing a promising new candidate strain as a biological control agent for controlling citrus canker.